Uncertainty altering the stock-gold correlation - Alakoski, Janne (My University, 2014)
The purpose of this study is to examine the effect of VIX index on stock-gold correlation. The motivation to study this relation relies on previous literature concerning flight-to-quality phenomenon, referring to capital shifting from troubled market to safer markets. This is often observed during crises periods, when uncertainty corners the market and correlations of equity markets are closing unity. This grown uncertainty causes investors to become more risk averse, and to look for alternative investments that would better hold their value in adverse market conditions. Gold is often believed to provide this needed quality and is considered as one of markets primary safe havens. Markets key measure for uncertainty is VIX index, which is often referred in financial media as the “fear gauge”. In this paper, stock-gold correlation is studied in relation to this uncertainty measure to examine whether uncertainty alters the comovement of stock and gold returns according to flight-to-quality phenomenon. The focus is set on United States markets and the data used runs from 1990 until the beginning of 2014. In the analysis part, first two time varying stock-gold correlation series are created, which are studied in relation to VIX index levels in bootstrapped subgroups. This is followed by regression analyses in which the effect of VIX index on stock-gold correlation during the most uncertain times is emphasized. Finally, VIX changes are studied along with contemporaneous stock and gold return comovements. The obtained results suggest that stock-gold correlation is negative on average, meaning that gold serves as a hedge for stocks. The relationship between stock and gold returns is also even more negative when VIX is at its highest levels, meaning that the decoupling of returns intensifies in times of increasing uncertainty. The results obtained in regression analyses also support the finding of gold serving as a hedge for stocks. However, regression results also imply that during periods of high uncertainty the decoupling of stock and gold returns weakens as VIX increases. Nevertheless, the effect of VIX still remain negative, implying that gold serves also as a safe haven for stocks in times when uncertainty is at its highest. Weeks of largest VIX increases are in turn accompanied with positive stock-gold correlation, which is however due to very low initial VIX values on the observed weeks.
Keywords: Stock-gold correlation; Flight-to-quality; VIX index; Safe haven; Gold; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|